SIMULASI PERAMBATAN GELOMBANG ELEKTROMAGNETIK PADA KRISTAL FOTONIK 2D MENGGUNAKAN METODE FINITE DIFFERENCE FREQUENCY DOMAIN - Adly Maulana Suherman; Teguh Puja Negara; Hendradi Hardhienata; Husin Alatas (Ilmu Komputer, FMIPA, Universitas Pakuan, 2019)
Numerical simulations on two-dimensional photonic crystals with defects were analyzed using the Finite Difference Frequency Domain (FDFD). This approach consists of Maxwell's formulation that uses Central Finite Difference to place fields and materials at discrete points of the Yee grid, so that the matrix wave equation is obtained in the form of column vectors. Absorbent boundary conditions use Perfectly Matched Layer (PML) with fictitious magnetic conductivity to shed incoming waves at the edge of the domain calculation. Photonic crystals can be assumed to be a periodic lattice of dielectric material that produces the phenomenon of photonic band gap (PBG). The results of FDFD simulations are compared with the literature with a difference of 0.056. This small difference value means that this method is good enough to analyze PBG phenomena. For point defects and the accumulation of electromagnetic waves, linear defects are investigated and analyzed with spectral responses. Insertion of defects in photonic crystals will produce a photonic pass band (PPB). The simulation results show that PPB depends on the angle of arrival vector, material permittivity, and width of the defect structure.